One-step formed solventless thick zinc-rich epoxy coating and method of making same

CN122941269APending Publication Date: 2026-10-20CHINA RAILWAY CONSTRUCTION ENGINEERING GROUP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610766008.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

目前常见厚涂涂层中常用的固化剂为聚酰胺,但在成膜过程中涂层因黏度过大会形成缺陷,且涂层在低温下难以固化,大大限制了厚涂涂层的应用场景

Benefits of technology

[0018]进一步的,低温固化的温度为-10~10℃,固化时间为20-24h。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention specifically relates to a one-time solvent-free thick-coat zinc-rich epoxy coating and its preparation method. The zinc-rich epoxy coating comprises the following raw materials in parts by weight: 25-30 parts epoxy resin, 2-5 parts reactive diluent, 10-18 parts curing agent, 0.1-0.8 parts leveling agent, 0.3-0.8 parts defoamer, 0.1-1 parts dispersant, 1-2 parts anti-settling agent, 12-16 parts flake zinc powder, 1-3 parts talc, and 1-2 parts imidazoline. This invention employs a solvent-free formulation design, resulting in extremely low VOCs, making it safe and environmentally friendly. Simultaneously, the precise design of the application characteristics and curing system allows for a single-application coating thickness exceeding 300 μm, offering wide application adaptability. This zinc-rich epoxy coating can cure at low temperatures and exhibits excellent adhesion to metal substrates, long-term corrosion resistance, and stable application performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of epoxy coating materials, specifically relating to a one-time forming solvent-free thick-coating zinc-rich epoxy coating and its preparation method. Background Technology

[0002] Epoxy zinc-rich coatings use high-zinc powder as the core of their anti-corrosion properties, combining sacrificial anode cathodic protection with the physical shielding of epoxy film formation for a dual anti-corrosion mechanism, resulting in significant protection for steel substrates. Due to its strong adhesion, good mechanical properties, impact resistance, and resistance to media corrosion, it is widely used in shipbuilding, offshore platforms, pipelines, and chemical equipment. However, even without defects such as cracks or voids, corrosive media can still penetrate the epoxy zinc-rich coating to some extent and corrode the metal substrate. Therefore, increasing the coating's density or thickness can effectively extend the penetration time of the media. Currently, for harsh, heavily corrosive environments, the total coating thickness is generally required to be above 300 μm, and commonly used heavy-duty anti-corrosion coatings are mostly solvent-based. Furthermore, multiple coats are usually required to achieve the specified film thickness and thus long-term heavy-duty anti-corrosion performance. However, this significantly increases construction costs and releases large amounts of organic solvents, leading to poor film formation, decreased coating anti-corrosion performance, environmental pollution, and irreversible damage to the health of construction workers.

[0003] Therefore, the development of one-piece solvent-free thick coatings is an important direction, which can not only effectively reduce construction costs but also improve the construction environment. Meanwhile, adding flake zinc to thick coatings to form solvent-free zinc-rich thick coatings is also an effective way to further extend the service life of the coating. Currently, polyamide is commonly used as a curing agent in thick coatings, but during the film-forming process, the coating will have defects due to excessive viscosity, and the coating is difficult to cure at low temperatures, which greatly limits the application scenarios of thick coatings. Summary of the Invention

[0004] To address the problems of the existing technology, this invention provides a one-step solvent-free thick-coating zinc-rich epoxy coating and its preparation method. Through a unique solvent-free formulation design, this invention enables the coating to cure at low temperatures, exhibits excellent film-forming properties, and is free of surface defects, thus achieving the requirements for one-step thick coating.

[0005] According to one aspect of the present invention, a one-time molding solvent-free thick-coating zinc-rich epoxy coating is provided, comprising the following raw materials in parts by weight: 25-30 parts epoxy resin, 2-5 parts reactive diluent, 10-18 parts curing agent, 0.1-0.8 parts leveling agent, 0.3-0.8 parts defoamer, 0.1-1 parts dispersant, 1-2 parts anti-settling agent, 12-16 parts flake zinc powder, 1-3 parts talc powder, and 1-2 parts imidazoline.

[0006] Furthermore, the epoxy resin is at least one of bisphenol A type epoxy resin E-88 and bisphenol A type epoxy resin E-54.

[0007] Furthermore, the active diluent is at least one of poly(propylene glycol) diglycidyl ether and neopentyl glycol diglycidyl ether.

[0008] Furthermore, the curing agent is at least one selected from polyamide and m-xyleneamine. Preferably, the curing agent is a compound of 8-12 parts polyamide and 2-6 parts m-xylene.

[0009] Furthermore, the amine value of the polyamide is 180-250 mg KOH / g. In this invention, when the amine value of the polyamide is too low, the reaction rate decreases significantly, the surface drying time is significantly prolonged, and the crosslinking network becomes loose, making it difficult to release internal stress; however, when the amine value of the polyamide is too high, it is prone to local overheating, and the pot life is significantly shortened, making it difficult to ensure effective leveling.

[0010] In this invention, the terminal epoxy groups of the epoxy resin undergo a nucleophilic ring-opening addition reaction with the curing agent. The curing agent is a combination of polyamide and m-xyleneamine. The difference in amine activity between polyamide and m-xyleneamine allows for complementary effects. m-xyleneamine has high reactivity and can rapidly crosslink at low temperatures; while polyamide has a slightly lower reaction rate, but its longer molecular chain and lower amine density extend its pot life, providing sufficient working time for thick-coating applications and achieving a one-step thick-coating effect. Furthermore, the rapid formation of the crosslinked backbone by m-xyleneamine, combined with the continuous penetration and filling of the crosslinked network by polyamide, results in gradient and uniform curing, effectively avoiding stress cracking caused by concentrated exothermic heating during curing. Additionally, polyamide exhibits excellent wettability and adhesion to metal surfaces, and the addition of m-xyleneamine improves the coating's corrosion resistance and promotes the dispersion of flake zinc powder. The shielding effect of the flake zinc powder significantly enhances the coating's adhesion and long-term corrosion resistance.

[0011] Furthermore, the leveling agent is at least one selected from polyether-modified polysiloxane, acrylate copolymer, and fluorocarbon-modified polyacrylate. Specifically, the polyether-modified polysiloxane includes BYK-333 and TEGO Glide 450, the acrylate copolymer includes BYK-354 and Modaflow 2100, and the fluorocarbon-modified polyacrylate includes BYK-358N and EFKA-3777.

[0012] Furthermore, the defoamer is at least one of BYK-1794, BYK-A555, BYK-1790, and AFCONA-2528.

[0013] Furthermore, the dispersant is a polyurethane dispersant, and the polyurethane dispersant is at least one of BYK-9076, EFKA-4550, and DISPERBYK-2155.

[0014] Furthermore, the anti-settling agent is at least one of polyamide wax and hydrophobic fumed silica.

[0015] Furthermore, the aspect ratio of the flake zinc powder is 60-120. In this invention, by limiting the aspect ratio of the flake zinc powder to the range of 60-120, the medium penetration path can be extended, the corrosion resistance can be improved, and the balance between construction and film quality can be taken into account, achieving a one-time thick coating without cracking.

[0016] In this invention, epoxy resin serves as the film-forming skeleton, and a bifunctional reactive diluent is selected to reduce the system viscosity and toughen the coating. The epoxy groups at the molecular ends participate in network crosslinking through chemical bonding. A blend of polyamide and m-xyleneamine is used as the curing agent to achieve a balance between curing rate, coating flexibility, and strength, enabling low-temperature curing and crack-free thick coatings. Imidazoline acts as a curing accelerator, corrosion inhibitor, and interface improver in the system. The shielding effect and cathodic protection of the flake zinc powder provide long-term corrosion protection for the metal substrate. Additives such as leveling agents, defoamers, and anti-settling agents help improve the coating's application and film-forming properties. This formulation is a solvent-free system with extremely low VOCs, making it safe and environmentally friendly, and achieving the requirements of low-temperature curing and one-time thick coating.

[0017] According to one aspect of the present invention, a method for preparing the above-mentioned one-time solvent-free thick-coated zinc-rich epoxy coating is provided, comprising the following steps: adding epoxy resin to a reaction vessel, adding an active diluent and stirring evenly, then sequentially adding a leveling agent, a defoamer, a dispersant, an anti-settling agent, and imidazoline and mixing evenly, then adding flake zinc powder and talc powder and stirring evenly, then adding a curing agent and stirring evenly, applying the resulting coating to the surface of an untreated metal substrate in one application, and finally curing at a low temperature to obtain the one-time solvent-free thick-coated zinc-rich epoxy coating.

[0018] Furthermore, the low-temperature curing temperature is -10~10℃, and the curing time is 20-24h.

[0019] Compared with existing technologies, the beneficial effects of this application are as follows: This invention adopts a solvent-free system formulation design, with extremely low VOCs, making it safe and environmentally friendly; at the same time, the precise design of the construction characteristics and curing system enables one-time film formation and thick coating, with a single application coating thickness exceeding 300μm, exhibiting wide construction adaptability. This zinc-rich epoxy coating can cure under low-temperature conditions and has high tolerance for metal substrate surface treatment, demonstrating excellent adhesion. Furthermore, the combination of flake zinc powder and talc provides an excellent shielding effect, achieving good corrosion resistance; the curing system obtained through the compound design of polyamide and m-xyleneamine has strong adhesion to metal substrates and synergistically improves the flexibility of the epoxy coating with the reactive diluent, while also exhibiting good leveling properties, making it less prone to appearance defects in thick coatings. Detailed Implementation

[0020] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention.

[0021] Example 1 This embodiment provides a one-time molding solvent-free thick-coating zinc-rich epoxy coating, comprising the following raw materials in parts by weight: 25 parts of bisphenol A type epoxy resin E-88, 2 parts of poly(propylene glycol) diglycidyl ether, 15 parts of curing agent, 0.5 parts of leveling agent, 0.5 parts of defoamer, 0.5 parts of dispersant, 1.5 parts of anti-settling agent, 15 parts of flake zinc powder, 2.5 parts of talc, and 1.5 parts of imidazoline.

[0022] Furthermore, the curing agent is a compound of 10 parts polyamide and 5 parts m-xyleneamine.

[0023] Furthermore, the leveling agent is BYK-333.

[0024] Furthermore, the defoamer is BYK-1794.

[0025] Furthermore, the dispersant is BYK-9076.

[0026] Furthermore, the anti-settling agent is hydrophobic fumed silica (brand name).

[0027] Furthermore, the aspect ratio of the sheet zinc powder is 60 (Hunan Xinweiling, XL-60).

[0028] In this embodiment, the preparation method of the above-mentioned one-time solvent-free thick-coated zinc-rich epoxy coating includes the following steps: according to the aforementioned formula, epoxy resin (bisphenol A type epoxy resin E-88) is added to a reaction vessel, and an active diluent (poly(propylene glycol) diglycidyl ether) is added and stirred for 5 minutes; then leveling agent (BYK-333), defoamer (BYK-1794), dispersant (BYK-9076), anti-settling agent (hydrophobic fumed silica), and imidazoline are added sequentially and mixed evenly, and then flaky zinc powder and talc powder are added and stirred evenly, with each raw material added and stirred for 5 minutes; then curing agent (polyamide, m-xyleneamine) is added and stirred for 5 minutes, and the resulting coating is applied to the surface of an untreated metal substrate in one go, and finally cured at 5°C for 24 hours to obtain the one-time solvent-free thick-coated zinc-rich epoxy coating.

[0029] Example 2 This embodiment provides a one-time molding solvent-free thick-coating zinc-rich epoxy coating, comprising the following raw materials in parts by weight: 30 parts of bisphenol A type epoxy resin E-88, 5 parts of neopentyl glycol diglycidyl ether, 18 parts of curing agent, 0.6 parts of leveling agent, 0.8 parts of defoamer, 0.8 parts of dispersant, 2 parts of anti-settling agent, 16 parts of flake zinc powder, 3 parts of talc, and 2 parts of imidazoline.

[0030] Furthermore, the curing agent is a compound of 12 parts polyamide and 6 parts m-xyleneamine.

[0031] Furthermore, the leveling agent is BYK-354.

[0032] Furthermore, the defoamer is BYK-1790.

[0033] Furthermore, the dispersant is EFKA-4550.

[0034] Furthermore, the anti-settling agent is polyamide wax.

[0035] Furthermore, the aspect ratio of the flaky zinc powder is 100 (Hunan Xinweiling, XL-100).

[0036] In this embodiment, the preparation method of the above-mentioned one-time solvent-free thick-coated zinc-rich epoxy coating includes the following steps: according to the aforementioned formula, epoxy resin (bisphenol A type epoxy resin E-88) is added to a reaction vessel, and an active diluent (neopentyl glycol diglycidyl ether) is added and stirred evenly. Then, leveling agent (BYK-354), defoamer (BYK-1790), dispersant (EFKA-4550), anti-settling agent (polyamide wax), and imidazoline are added sequentially and mixed evenly. Then, flaky zinc powder and talc powder are added and stirred evenly. Subsequently, curing agent (polyamide, m-xyleneamine) is added and stirred evenly. The resulting coating is applied to the surface of an untreated metal substrate in one go, and finally cured at 5°C for 24 hours to obtain the one-time solvent-free thick-coated zinc-rich epoxy coating.

[0037] Example 3 This embodiment provides a one-time molding solvent-free thick-coating zinc-rich epoxy coating, comprising the following raw materials in parts by weight: 28 parts epoxy resin, 3 parts poly(propylene glycol) diglycidyl ether, 14 parts curing agent, 0.4 parts leveling agent, 0.6 parts defoamer, 0.8 parts dispersant, 1.2 parts anti-settling agent, 14 parts flake zinc powder, 2 parts talc powder, and 1.5 parts imidazoline.

[0038] Furthermore, the curing agent is a compound of 10 parts polyamide and 4 parts m-xyleneamine.

[0039] Furthermore, the leveling agent is BYK-358N.

[0040] Furthermore, the defoamer is BYK-A555.

[0041] Furthermore, the dispersant is DISPERBYK-2155.

[0042] Furthermore, the anti-settling agent is hydrophobic fumed silica (brand name).

[0043] Furthermore, the aspect ratio of the flaky zinc powder is 80 (Hunan Xinweiling, XL-80).

[0044] In this embodiment, the preparation method of the above-mentioned one-time solvent-free thick-coated zinc-rich epoxy coating includes the following steps: according to the aforementioned formula, epoxy resin (bisphenol A type epoxy resin E-54) is added to a reaction vessel, and an active diluent (poly(propylene glycol) diglycidyl ether) is added and stirred evenly. Then, leveling agent (BYK-358N), defoamer (BYK-A555), dispersant (DISPERBYK-2155), anti-settling agent (hydrophobic fumed silica), and imidazoline are added sequentially and mixed evenly. Then, flaky zinc powder and talc powder are added and stirred evenly. Subsequently, curing agent (polyamide, m-xyleneamine) is added and stirred evenly. The resulting coating is applied to the surface of an untreated metal substrate in one go, and finally cured at 5°C for 24 hours to obtain the one-time solvent-free thick-coated zinc-rich epoxy coating.

[0045] Example 4 The difference between this embodiment and Embodiment 1 is that this embodiment uses 12 parts of curing agent, which is composed of 10 parts of polyamide and 2 parts of m-xyleneamine, while the rest is the same as in Embodiment 1.

[0046] Example 5 The difference between this embodiment and Embodiment 1 is that this embodiment uses 13 parts of curing agent, which is composed of 10 parts of polyamide and 3 parts of m-xyleneamine, while the rest is the same as in Embodiment 1.

[0047] Example 6 The difference between this embodiment and Embodiment 1 is that this embodiment uses 14 parts of curing agent, which is composed of 10 parts of polyamide and 4 parts of m-xyleneamine, while the rest is the same as in Embodiment 1.

[0048] Example 7 The difference between this embodiment and Embodiment 1 is that this embodiment uses 16 parts of curing agent, which is composed of 10 parts of polyamide and 6 parts of m-xyleneamine, while the rest is the same as in Embodiment 1.

[0049] Comparative Example 1 The difference between this comparative example and Example 1 is that this comparative example uses 10 parts of curing agent, all of which are polyamides, i.e. no m-xyleneamine is added, and the rest is the same as in Example 1.

[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that this comparative example uses 15 parts of curing agent, all of which are polyamide, while the rest is the same as in Example 1.

[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that this comparative example uses 20 parts of curing agent, all of which are polyamide, while the rest is the same as in Example 1.

[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that this comparative example uses 15 parts of m-xyleneamine instead of the curing agent in Example 1.

[0053] Comparative Example 5 The difference between this comparative example and Example 1 is that this comparative example uses spherical zinc powder (Hunan Xinweiling, QX-16) instead of the flake zinc powder in Example 1.

[0054] Comparative Example 6 The difference between this comparative example and Example 1 is that no imidazoline was added to this comparative example, while the rest is the same as in Example 1.

[0055] Comparative Example 7 The difference between this comparative example and Example 1 is that this comparative example uses an equal amount of benzyl alcohol to replace the poly(propylene glycol) diglycidyl ether in Example 1.

[0056] This invention characterizes the performance of the solvent-free, thick-film zinc-rich epoxy coatings prepared in the above embodiments and comparative examples. Specifically, the VOC content of the coating was tested according to GB / T 23986.2-2023 "Determination of Volatile Organic Compounds (VOCs) and / or Semi-Volatile Organic Compounds (SVOCs) Content in Paints and Varnishes - Part 2: Gas Chromatography"; the coating film thickness was tested according to GB / T 13452.2-2008 "Determination of Film Thickness of Paints and Varnishes"; to further visualize the coating thickness, a handheld thickness gauge was also used to confirm the coating thickness; the adhesion between the coating and the substrate was tested according to GB / T 5210-2006 "Paints and Varnishes - Pull-Off Adhesion Test"; the coating hardness was tested according to GB / T 6739-2022 "Determination of Film Hardness of Paints and Varnishes - Pencil Method"; and the coating impact resistance was tested according to GB / T The coating was tested according to GB / T 1732-2020 "Determination of Impact Resistance of Paint Films"; the surface drying time and complete drying time of the coating were tested according to GB / T 1728-2020 "Determination of Drying Time of Paint Films and Putty Films"; the seawater corrosion resistance of the coating was tested for 720 hours according to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test" (Neutral Salt Spray Test), using 5% sodium chloride, pH 6.5-7.2, and temperature 35±2℃. The surface appearance of the sample was observed. If pitting, cracks, bubbles, rust, or peeling appeared, it was considered unqualified; if there were no corrosion defects on the surface, it was considered qualified. The specific test results are shown in the table below:

[0057] As shown in the table above, this invention optimizes the solvent-free formulation of epoxy resin, resulting in low VOC content, safety, and environmental friendliness. It achieves thick film formation in a single application, with a coating thickness exceeding 300 μm, demonstrating broad application adaptability. This zinc-rich epoxy coating can cure at low temperatures, achieving a balance between long-term corrosion resistance and stable application. A comparison of Example 1 and Comparative Examples 1-4 shows that this invention, by using polyamide and m-xyleneamine synergistically as curing agents, can meet the requirements of thick film formation in a single application and low-temperature curing.

[0058] In addition, seawater corrosion resistance tests were conducted on the coatings of Example 1 and Comparative Examples 4-7. The coating of Comparative Example 4 showed slight cracks; while the coating of Comparative Example 5 exhibited significant deterioration in seawater corrosion resistance, with localized blistering on its surface. This was mainly due to the weak shielding effect of the spherical zinc powder and the reduced effective coverage area for the same weight, leading to a decrease in cathodic protection efficiency. Comparative Example 6 showed that when the flake zinc powder lacked the synergistic corrosion inhibition of imidazoline, the coating relied solely on the cathodic protection of the flake zinc powder, gradually developing blistering during the salt spray test, indicating a significant decrease in seawater corrosion resistance. In Example 1, however, imidazoline could form a hydrophobic film on the metal matrix and the surface of the flake zinc powder, effectively inhibiting seawater corrosion. Comparative Example 7 showed that using benzyl alcohol instead of poly(propylene glycol) diglycidyl ether prevented it from participating in the crosslinking film formation process, reducing the coating's density and causing pitting corrosion to appear in the early stages of the salt spray test, indicating a decrease in the long-term seawater corrosion resistance of this coating.

[0059] The specific embodiments described above are further illustrations of the technical solution and beneficial effects of the present invention, and are not intended to limit the implementation methods. For those skilled in the art, any obvious substitutions without departing from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A one-piece, solvent-free, thick-coat zinc-rich epoxy coating, characterized in that, The raw materials include the following parts by weight: 25-30 parts epoxy resin, 2-5 parts reactive diluent, 10-18 parts curing agent, 0.1-0.8 parts leveling agent, 0.3-0.8 parts defoamer, 0.1-1 parts dispersant, 1-2 parts anti-settling agent, 12-16 parts flake zinc powder, 1-3 parts talc, and 1-2 parts imidazoline.

2. The one-piece solvent-free thick-coat zinc-rich epoxy coating as described in claim 1, characterized in that, The epoxy resin is at least one of bisphenol A type epoxy resin E-88 and bisphenol A type epoxy resin E-54.

3. The one-piece solvent-free thick-coat zinc-rich epoxy coating as described in claim 1, characterized in that, The active diluent is at least one of poly(propylene glycol) diglycidyl ether and neopentyl glycol diglycidyl ether.

4. The one-piece solvent-free thick-coat zinc-rich epoxy coating as described in claim 1, characterized in that, The curing agent is at least one of polyamide and m-xyleneamine.

5. The one-piece solvent-free thick-coat zinc-rich epoxy coating as described in claim 1, characterized in that, The curing agent is a compound of 8-12 parts polyamide and 2-6 parts m-xylene.

6. The one-piece solvent-free thick-coat zinc-rich epoxy coating as described in claim 1, characterized in that, The leveling agent is at least one of polyether-modified polysiloxane, acrylate copolymer, and fluorocarbon-modified polyacrylate; the defoamer is at least one of BYK-1794, BYK-A555, BYK-1790, and AFCONA-2528.

7. The one-piece solvent-free thick-coat zinc-rich epoxy coating as described in claim 1, characterized in that, The dispersant is a polyurethane dispersant, and the polyurethane dispersant is at least one of BYK-9076, EFKA-4550, and DISPERBYK-2155; the anti-settling agent is at least one of polyamide wax and hydrophobic fumed silica.

8. The one-piece solvent-free thick-coat zinc-rich epoxy coating as described in claim 1, characterized in that, The aspect ratio of the sheet zinc powder is 60-120.

9. The method for preparing a one-time solvent-free thick-coating zinc-rich epoxy coating as described in any one of claims 1-8, characterized in that, The process includes the following steps: adding epoxy resin to a reaction vessel, adding an active diluent and stirring until homogeneous, then adding a leveling agent, defoamer, dispersant, anti-settling agent, and imidazoline in sequence and mixing until homogeneous, then adding flaky zinc powder and talc powder and stirring until homogeneous, followed by adding a curing agent and stirring until homogeneous, applying the resulting coating to the surface of an untreated metal substrate in one application, and finally curing at a low temperature to obtain the one-time solvent-free thick-coat zinc-rich epoxy coating.

10. The method for preparing a one-step solvent-free thick-coating zinc-rich epoxy coating as described in claim 9, characterized in that, The low-temperature curing temperature is 5℃, and the curing time is 20-24h.